Contributing Factors of the Choice of Poultry Waste Management Practices: Evidence from Nigeria - Theophilus Miebi, Gbigbi (International Journal of Environment, Agriculture and Biotechnology, 2020)
The research was conducted to evaluate the choice of management practices for poultry wastes in Delta State. A multistage sampling procedure was used to obtain data from 133 respondents. A well structured questionnaire was used for the study. Data were analyzed using descriptive statistics, cost and return analysis and binary logit. Results showed that 70.9% were male with an average age of 44 years. About 73.0% were married with 99.0% acquiring formal education. The mean household size was 5 persons with mean farming experience of 6 years. Burying and burning were the primary waste management practices employed. The binary logit result indicates that age (p<0.05), educational level (p<0.05), household size (p<0.05), type of bird (p<0.05) and poultry housing method (p<0.05) were positively significant while marital status (p<0.05) was negatively significant among the factors affecting the choice of poultry waste management practices by the farmers in the study area. The major challenges in managing poultry waste were inadequate information, weather condition, lack of convenient dumping space and unavailability of litter material.